Trade Openness, Financial Development and Economic Growth in Lesotho: BVAR and Time-varying VAR Analysis - Sanusi, Kazeem Abimbola; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2024)
This research paper explores the dynamic relationship between trade openness, financial development, and economic growth in Lesotho. The study utilizes quarterly time series data spanning from 1970 to 2021, obtained from the Central Bank of Lesotho. This paper makes a significant contribution to the methodological discourse by utilizing a time-varying VAR approach, in addition to the Bayesian VAR estimation approach. The empirical results indicate that there is no cointegration relationship between economic growth, financial development, and trade openness. However, the evidence shows a unidirectional causality from economic growth to trade openness in Lesotho. The Bayesian VAR and time-varying VAR estimations reveal that the variables dynamically react and adjust to shocks among the variables. The study recommends that to stimulate the opening up of the economy to the world, growth-enhancing policies such as the provision of world-class infrastructure facilities, improved healthcare facilities, and a conducive macroeconomic environment should be implemented, considering the insufficient international demand in Lesotho.